Human trafficking and the growing malady of disinformation - Prakash, Jaya; Erickson, Timothy B.; Stoklosa, Hanni (Frontiers in Public Health, 2022)
Disinformation has endangered the most vulnerable communities within our world. The anti-trafficking movement in particular has been adversely impacted by disinformation tactics advanced through the QAnon campaign. QAnon’s extremist messaging exacerbates gendered, racist, and xenophobic manifestations of trafficking victimization as well as problematic responses to trafficking that underpin historic structural inequities built into the United States’ response to trafficking. We describe an overview of mechanisms used by the QAnon campaign to spread disinformation and illustrate how these mechanisms adversely affect the anti-trafficking movement. Given the critical role of healthcare providers in both the identification and connection to care for trafficked persons, as well as their susceptibility to disinformation, we provide several recommendations for the health sector to leverage their educational and advocacy power to combat trafficking disinformation while addressing the root causes of human trafficking.